Millennials: New Environments and the Human Right to Work (Journal of Applied Business and Economics, 2020)
This study will be limited to the examination of the human right to work as corresponding to the generation of the so-called Millennials. We will present a new working mode that is being conducted today through the use of new technologies: the so-called telework. Then, we will define who we refer to with the term Millennials, and a sketch of the social context in which the members of that generation live will be made, explaining how this new pragmatic environment has a significant impact on the working environment in which they carry out their activities, prompting the emergence of new requirements with respect to the improvement of the working conditions in which they develop their economic activities day by day. Finally, an analysis will be made of two modern institutions that, in the current work environment, have been built on the basis of Millennials' practices: the freelance and the startups.
Keywords: Business; Economics; millennials; human right to work; internet; telework; freelance; startups